Prediction model of overweight and obesity in primary school children in urban areas - Harjatmo, Titus Priyo; Marbun, Rosmida M.; Puspitaningtyas, Ratih (International Journal Of Community Medicine And Public Health, 2020)
Background: Overweight and obesity can occur both in children to adulthood. The prevalence of obesity for children aged 5-12 years is still high at 18.8% consisting of 10.8% overweight and obese at 8.8%. The prevalence of childhood obesity has increased in various countries including Indonesia. The results of previous data collection shows that the proportion of fat and obesity is quite high at 34.5%. Methods: This type of research is a cross sectional study because the independent and dependent variables are measured at the same time. The sample was a portion of elementary school children in SD Kramat Pela Kebayoran Baru. Case samples are elementary school children who are overweight and obese (weight/height >1.0 SD) as many as 35 children and the control sample is elementary school children with normal weight/height ≤1.0 SD as many as 35 children. Results: From the results of the analysis of physical activity variables showed that the group of children who are overweight or obese have an average activity lower than normal school children. Odds ratio analysis shows that the risk of being obese or obese is 18.1 times in inactive children compared to active ones (95% CI: 4.60-70.9). Screen time analysis with the incidence of obesity did not show significance. Conclusions: Growth monitoring needs to be pursued regularly so that efforts to control obesity in school children can be done.